2012
DOI: 10.2174/138920012802138598
|View full text |Cite
|
Sign up to set email alerts
|

Catabolic Fate and Pharmacokinetic Characterization of Trastuzumab Emtansine (T-DM1): an Emphasis on Preclinical and Clinical Catabolism

Abstract: Trastuzumab emtansine (T-DM1) is an antibody-drug conjugate in clinical development for the treatment of human epidermal growth factor receptor 2 (HER2)-positive cancers. Herein, we describe a series of studies to assess T-DM1 absorption, distribution, metabolism, and excretion (ADME) in rats as well as to assess human exposure to T-DM1 catabolites. Following administration of unlabeled and radiolabeled T-DM1 in female Sprague Dawley rats as a single dose, plasma, urine, bile and feces were assessed for mass b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
114
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(123 citation statements)
references
References 11 publications
(13 reference statements)
9
114
0
Order By: Relevance
“…The anti-CanAg-SMCC-[ 3 H]DM1 conjugate with an uncleavable linker was found to have a similar distribution profile in tumor-bearing mice as shown above (Fig. 3c) for a disulfide-linked conjugate (unpublished data), and was also similar to the tissue distribution reported for labeled maytansinoid in nontumorbearing rats following administration of a single bolus administration of T-[ 3 H]DM1 (30,31). In the study with T-DM1 (31), up to 80% of the radioactivity was recovered in the feces over 7 days consistent with the hepatobiliary route for maytansinoid elimination.…”
Section: Tissue Distributionsupporting
confidence: 77%
“…The anti-CanAg-SMCC-[ 3 H]DM1 conjugate with an uncleavable linker was found to have a similar distribution profile in tumor-bearing mice as shown above (Fig. 3c) for a disulfide-linked conjugate (unpublished data), and was also similar to the tissue distribution reported for labeled maytansinoid in nontumorbearing rats following administration of a single bolus administration of T-[ 3 H]DM1 (30,31). In the study with T-DM1 (31), up to 80% of the radioactivity was recovered in the feces over 7 days consistent with the hepatobiliary route for maytansinoid elimination.…”
Section: Tissue Distributionsupporting
confidence: 77%
“…The thiosuccinimide linkage may undergo a maleimide elimination reaction and transfer the drug linker to other components of the plasma with reactive thiol (Shen et al, 2012a). This transfer has been observed for ADCs; however, the circulating concentrations of these species are appreciably lower than that of ADC, suggesting that other mechanisms may compete with maleimide transfer such as proteolytic cleavage in cells or hydrolysis of the linker.…”
Section: Antibody-drug Conjugate Stabilitymentioning
confidence: 96%
“…Based on preclinical data, the major elimination pathway of DM1-containing catabolites in rats after ado-trastuzumab emtansine administration is the fecal/biliary route. About 80% of radioactivity was recovered in the feces, and 50% was recovered in the bile (Shen et al, 2012a). A clinical excretion study of brentuximab vedotin showed that over a 1-week period the primary excretion route of MMAE was via feces, which accounted for approximately 72% of the recovered MMAE, with the remaining MMAE recovered in urine (Han et al, 2013a).…”
Section: Eliminationmentioning
confidence: 99%
See 2 more Smart Citations